Inhibitory effects of Swietenia macrophylla on myotoxic phospholipases A2 (2013)
ABSTRACT: Activity-guided fractionation of an ethanol-soluble extract of the leaves of Swietenia macrophylla King, Meliaceae, led to several fractions. As a result, sample Sm13-16, 23 had the most promising activity against phospholipases A2 (PLA2), Asp49 and Lys49 types. This fraction inhibited PLA2 activity of the Asp49 PLA2, when aggregated substrate was used. On the other hand, this activity was weakly neutralized when monodispersed substrate was used. In addition, Sm13-16, 23 inhibited, in a dose dependent manner, the cytotoxicity, myotoxicity and edema induced by PLA2s, as well as the anticoagulant activity of Asp49 PLA2. Overall, this fraction exhibited a better inhibition of the toxic activities induced by the Lys49 PLA2 than those caused by the Asp49 PLA2. The spectral data of Sm13-16, 23 suggested the presence of aromatic compounds (UV λ max (nm) 655, 266, and 219; IR λ max KBr (cm-1): ~ 3600-3000 (OH), 2923.07 and 1438.90 (C-H), 1656.69 (C = O), 1618.63 and 1607.67 (C-O), 1285.47- 772.60). We suggest that phenolic compounds could interact and inhibit the toxins by several mechanisms. Further analysis of the compounds present in the active fraction could be a relevant contribution in the treatment of accidents caused by snake envenomation.